SAFES Clinical Practices Recommendations for Management of Hypothyroidism and Hyperthyroidism - Bajaj, Sarita; Muthukuda, Dimuthu; Afsana, Faria; Qureshi, Nazmul Kabir; Shaikh, Shehla; Samarasekara, Tharanga; Subasinghe, Chandrika J; Shakya, Amit; Shrestha, Dina (Journal of Diabetes and Endocrinology Association of Nepal, 2026)
Not available